Preserving Traditional Games of Margala through Tourism Saka Activities in Toba Samosir District - Siregar, Ernawati Hadi Suriyani; Gultom, Ibrahim; Baiduri, Ratih (Indonesian Journal of Social Science Research, 2022)
Aim: This study aims to describe an activity that involves Scouting activities, namely Saka Pariwisata, in preserving traditional games, especially the traditional game of Margala in Toba Samosir Regency. Method: This research used a qualitative descriptive approach. The problem-solving method is carried out by participatory observation through the Tourism Saka Camp activities. The steps are situation analysis, socialization, and implementation of the traditional game of margala. The author mingles in Saka Tourism activities during the activity. Determination of informants by purposive sampling by taking 3 (three) Scout members who are members of Saka Pariwisata who participate in traditional game activities. Result: Based on the data, it can be explained that the first informant said that the Saka Wisata activities in preserving the Margala game in Toba Regency had a positive impact because the Saka Tourism Scout Members in Toba Regency began to be involved in the preservation of traditional games by making and participating in events and inviting other youth to participate in the game traditional. The second informant added that adolescents who are members of Saka Pariwisata began to slowly switch from playing gadgets online to traditional games with high cultural value. Furthermore, the third informant explained that the effort to inherit the traditional game of margala was to invite other youth to participate in Saka Pariwisata sustainably. After this activity, it is hoped that teenagers will no longer be addicted to playing online gadgets that have proven insufficient for health.